Valoración anatómica, histológica, tomográfica y ultrasonográfica del músculo vasto lateral en caninos sanos - Mercado, M. (2003)
Muscle diseases are not common in dogs, but when they appear they are difficult to diagnose. For their diagnosis it is necessary to appeal to complementary methods, such as the measurement of serum muscle enzymes, electromyography, ultrasonography and mainly muscle biopsy, since most of the muscular lesions can only be detected by microscopy. To be able to interpret the biopsy results it is necessary to have a thorough knowledge of normal muscle structure. The present work describes the macroscopic anatomy and the muscular ultrastructure of the canine vastus lateralis muscle. This muscle was chosen because along with the cuadriceps group, it is the most affected muscular group in hindlimb lesions.